The Role of Gut Microbiota Dysbiosis as a Potential Factor in Early Diagnosis, Prognosis and Therapeutic Strategy of COVID-19 Patients - Kevin Tandarto; Kadek Ari Suyandi; Lily Chandrawati (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the most widespread global pandemic since the 1918 influenza pandemic. The consequences of the coronavirus disease 2019 (COVID-19) are devastating and become the current world major public health issue. Not only SARS-CoV-2 attack the respiratory system, but also can affect multiple organs. Clinical manifestation varies from asymptomatic to severe multiorgan dysfunctions. COVID-19 is typically associated with a set of comorbidities such as hypertension, diabetes, obesity, and/or advanced age, which significantly exacerbates the consequences of infection. During the early stages of the disease, SARS-CoV-2 can also cause gastrointestinal symptoms such as vomiting, diarrhea, or abdominal pain. Intestinal dysfunction alters intestinal microbes and increases inflammatory cytokines. As a result, diagnosing gastrointestinal symptoms that procede respiratory problems during COVID-19 infection may be required for better early diagnosis and treatment. Discovering the composition of the microbiota and its metabolic products in the context of COVID-19 can aid in the identification of novel disease biomarkers and therapeutic targets. In the context of COVID-19, elucidating changes to the microbiome as reliable biomarkers represents an overlooked piece of the disease puzzle that requires further investigation.